2015
DOI: 10.3389/fendo.2014.00225
|View full text |Cite
|
Sign up to set email alerts
|

Non-Genomic Androgen Action Regulates Proliferative/Migratory Signaling in Stromal Cells

Abstract: Prostate cancer (PCa) is the major cause of cancer-related death among the male population of Western society, and androgen-deprivation therapy (ADT) represents the first line in PCa treatment. However, although androgen receptor (AR) expression is maintained throughout the various stages of PCa, ADT frequently fails. Clinical studies have demonstrated that different androgen/AR signaling pathways operate in target tissues. AR stimulates growth and transformation of target cells, but under certain conditions s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…In accordance with previous reports in prostate cancer fibroblasts [24], we observed that AR is expressed in breast cancer stromal cells. Although there are indications that high AR levels may be associated with response to chemotherapy [18], stromal AR mRNA was not differentially expressed in DS vs. NDS samples.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with previous reports in prostate cancer fibroblasts [24], we observed that AR is expressed in breast cancer stromal cells. Although there are indications that high AR levels may be associated with response to chemotherapy [18], stromal AR mRNA was not differentially expressed in DS vs. NDS samples.…”
Section: Discussionsupporting
confidence: 93%
“…Studies in prostate cancer have reported on many mechanisms of rapid non genomic 2nd messenger signaling following exposure to androgens ( 117 , 118 ). Furthermore, non-genomic AR signaling has been reported in the sertoli cells of the testes ( 119 ), fibroblasts ( 106 ), osteoblasts and osteocytes ( 120 ), stromal cells ( 121 ), and breast cancer cells. ERα and AR have been shown to directly interact with the SH2 and SH3 domain respectively of Src.…”
Section: Ar Localization Non-genomic Signaling and Functional Conseqmentioning
confidence: 99%
“…These cells have, in most cases, been considered androgen insensitive because of their very low AR expression level, and hence the absence of AR-mediated gene transcription. Nonetheless, they still respond to androgens with activation of signaling effectors [ 105 ]. Moreover, the findings so far reported on AR expression in prostate SCs or CSCs do not exclude that membrane AR might be expressed in these cells.…”
Section: Ar In Prostate Scs and Cscsmentioning
confidence: 99%